2009
DOI: 10.1002/pssa.200925095
|View full text |Cite
|
Sign up to set email alerts
|

Transport and recombination kinetics in TlGaTe2 crystals

Abstract: In this work, the transport and recombination mechanisms as well as the average hole‐relaxation time in TlGaTe2 have been investigated by means of temperature‐dependent dark electrical conductivity, photoexcitation intensity‐dependent photoconductivity, and Hall effect measurements, respectively. The experimental data analysis revealed the existence of a critical temperature of 150 K. At this temperature, the transport mechanism is disturbed. The dark conductivity data analysis allowed the determination of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…For the indirect electronic transition, we found that the effective mass of electrons is 0.196 me (me–a mass of an electron) along the M|X-P direction and the effective mass of holes is 0.736 me along the Z1-M direction. It is interesting to note that Qasrawi et al used the Hall effect measurement and reported the hole effective mass of TlGaTe 2 to be 0.730 me [7], which is in good agreement with our calculated hole effective mass (0.736 me). For the direct transition, we noted that the EM of electrons is 0.378 me and EM of holes is 0.736 me at Z-point.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For the indirect electronic transition, we found that the effective mass of electrons is 0.196 me (me–a mass of an electron) along the M|X-P direction and the effective mass of holes is 0.736 me along the Z1-M direction. It is interesting to note that Qasrawi et al used the Hall effect measurement and reported the hole effective mass of TlGaTe 2 to be 0.730 me [7], which is in good agreement with our calculated hole effective mass (0.736 me). For the direct transition, we noted that the EM of electrons is 0.378 me and EM of holes is 0.736 me at Z-point.…”
Section: Resultssupporting
confidence: 89%
“…Thallium-bearing ternary materials have been studied in optoelectronics [5], but not extensively investigated in photovoltaics due to the fact that thallium is toxic. Researchers have shown interest to the Hall effect analysis, the photoconductivity and recombination kinetics in dichalcogenide-TlGaTe 2 material [6,7]. From our earlier study on non-silicon solar cell materials [8], we identified that TlGaTe 2 has a strong absorption coefficient in the visible region, but a complete study of TlGaTe 2 is needed to confirm that it is potential material for PV applications.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the trap energy level being 0.26 eV which was determined from the J−V plots of the a-axis measurement coincides with that determined from (the ohmic region measurements) resistivity analysis along the c-axis [10]. In spite of the pronounced anisotropy of the crystal, the same energy levels appears to exist along both directions, it only diers in the temperature domination region.…”
Section: Resultssupporting
confidence: 82%
“….20 cm, ϵ s = 14.8 [16], g = 2 which are reported in the previous works [9,10], the hole trap density values were calculated at room temperature from Eq. (4) and found to be 5.6 × 10 10 cm −3 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation